2021
DOI: 10.3390/biomedicines9121950
|View full text |Cite
|
Sign up to set email alerts
|

Complement and Coagulation System Crosstalk in Synaptic and Neural Conduction in the Central and Peripheral Nervous Systems

Abstract: Complement and coagulation are both key systems that defend the body from harm. They share multiple features and are similarly activated. They each play individual roles in the systemic circulation in physiology and pathophysiology, with significant crosstalk between them. Components from both systems are mapped to important structures in the central nervous system (CNS) and peripheral nervous system (PNS). Complement and coagulation participate in critical functions in neuronal development and synaptic plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 145 publications
(179 reference statements)
0
7
0
Order By: Relevance
“…In order to defend the body from harm, complement and coagulation play an important role. Each plays a different role in physiology and pathophysiology of the systemic circulation, but their functions are interconnected [34]. SERPINA5 regulates hemostasis and thrombosis across multiple organs.…”
Section: Discussionmentioning
confidence: 99%
“…In order to defend the body from harm, complement and coagulation play an important role. Each plays a different role in physiology and pathophysiology of the systemic circulation, but their functions are interconnected [34]. SERPINA5 regulates hemostasis and thrombosis across multiple organs.…”
Section: Discussionmentioning
confidence: 99%
“…Double immunofluorescence staining confirmed the colocalization of PAR1 and GFAP in the central part of the TREZ, which suggests that PAR1 might mediate astrocyte activation during the pathogenesis of TN. A previous study reported that perinodal astrocytes regulate the proteolysis of NF155 by thrombin via PN-1 secretion (Berkowitz et al, 2021). In addition, a variety of glial cells, including astrocytes, normally insert themselves into the nodes of Ranvier to regulate structural plasticity and signal conduction (Serwanski et al, 2017;Jha et al, 2019;Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, C1q is required for normal neuronal maturation, as it directs microglia to synapses to be eliminated in the process of synaptic pruning [49][50][51] . C1q expression is upregulated in neuronal injury and early in neurodegenerative disorders such as AD.…”
Section: Immune Functions Of C1qmentioning
confidence: 99%